Mother language interference in written texts in english as a foreign language - Quishpe Hipo, Luis (2020)
English is taught as a compulsory subject in Ecuadorian universities; however, written production conveys incorrect messages due to limited linguistic knowledge. The objective research was to describe the most significant interference errors from L1 on L2 in narrative texts written by the EFL learners of the second level at Medicine School during the academic year October 2018 - July 2019, ESPOCH, Riobamba, Ecuador. A non-experimental research of descriptive cross-sectional study with a mix approach, socio-educational modality supported by field, documentary and content analysis research were applied. The population was made up of 109 learners and 04 teachers; the probabilistic stratified type sampling was 86 students. For gathering information applied a survey with its questionnaire and a writing test with its narrative text. The information was processed in spreadsheets and analyzing by descriptive statistics using frequencies and percentages. Error Analysis comparison was applied to revise narrative texts. The results determined that the most significant interference errors were both: Grammatical included overuse of articles, misuse of verbs, omission of the personal pronouns, incorrect word order and Lexical included misuse of prepositions and false cognates. To sum up, language transfer from L1 to L2 constitute an obstacle to achieve written texts production efficiently.